Textbook Project on Social Problems Using Case Method - Melda Oktika; Hidayat Hidayat; Samsidar Tanjung (Randwick International of Education and Linguistics Science Journal, 2023)
This research aims to: (1) produce a suitable case method-based social problems textbook for class V at SD Negeri 056627 Kwala Sawit District. Batang Attack District. Langkat, (2) produce an effective social problems textbook based on the case method in class V of SD Negeri 056627 Kwala Sawit District. Batang Attack District, (3) Steps to become better textbook In this research refers to the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) research and development model. The results of the research show that case method-based social problems textbooks are very suitable for use. This is proven by material experts with a percentage of 94%, language experts 90% and design experts 78%. The social problems textbook based on the case method is very effective applied to improve student learning outcomes at SD Negeri 056627 Kwala Sawit, Batang Attack District, Langkat City based on the completeness test, student learning outcomes were 91.66% (very good) and the n-gain score increased student learning outcomes by g= 0.75 (high)